Adsorption of Chromium Using Apu Wood (Pistia stratiotes L) Root Bioadsorbent and Modification of Apu Wood Root - Hargono Hargono; David Joeventus C.S.W.; Devia Winisar; Muhammad Fahmi Zakaria (Universitas Ahmad Dahlan, 2022)
The adsorbent is a material used for the adsorption process. One alternative used in the selection of adsorbents is biological materials. One type of plant that can be used to adsorb heavy metals is Apu Wood. This study aims to examine the effect of Cr (VI) concentration on the adsorption capacity of adsorbent, examine the time adjustment to the adsorption capacity of adsorbent, examine the characterization of adsorbent using SEM and FTIR, assess the adsorption equilibrium using the Langmuir and Freundlich methods and the kinetics of the adsorption reaction using pseudo order 1 and pseudo order 2. In this study, variables are the concentration of initial solution Cr(VI) of 2, 4, 6, 8, and 10 ppm and contact time of 15, 30, 45, 60, and 75 minutes. The result of this research is the capacity of adsorption increases in line with the increase in the initial concentration of Cr(VI) solution as adsorbate. Contact time affects the capacity of adsorption where the longer the contact time, the adsorption capacity increases until it reaches equilibrium at 70 minutes. In SEM and FTIR analysis both tests showed that aluminum adsorbtion using apu wood adsorbent and its modification changed the composition of the function group and the structure of the adsorbent surface area. The Langmuir Isoterm model produces a greater value R2 than the Freundlich isotherm model which indicates that the adsorbent surface is in direct contact with adsorbate and adsorbate attaches to the active site of the adsorbent of only one layer (monolayer). Kinetics adsorption pseudo order 1 produces a value of R2 greater than kinetics adsorps pseudo order 2 which indicates the mechanism that occurs is the transfer of mass in addition to the use of electrons together between heavy metals Cr (VI) with apu wood root.